Lateral transperitoneal laparoscopic management for paragangliomas in para-aortic position: Surgical experience from case reports of three patients - Ngoc Hung Nguyen; Huy Du Nguyen; Hai Dang Do; Tuan Hiep Luong; Thanh Khiem Nguyen (Vietnam Journal of Science, Technology and Engineering, 2022)
Paragangliomas are a type of neuroendocrine tumour with catecholamine secretion outside of the adrenal medulla. These tumours are frequently found in the para-aortic region, which makes them difficult to manage laparoscopically. We herein present a case report of three patients with paragangliomas in a difficult superior para-aortic position. All cases had symptoms of catecholamine release with uncontrolled episodic hypertension and had their tumours successfully removed by transperitoneal laparoscopic management. We have found this method to be a suitable approach because it reveals a wide surgical field and a view over all organs, especially blood vessels around the tumour. Although blood and urine dopamine and noradrenaline levels were not measured postoperatively, all three patients were discharged without complication and they did not display any more clinical symptoms. Lateral transperitoneal laparoscopic surgery provided a wide field of view, which clearly revealed the tumour and surrounding components indicating it is one of the safest and most effective approaches, especially for paragangliomas adjacent to large blood vessels.